Effect of intravaginal electrical stimulation on pelvic floor muscle strength - Amaro, João Luiz [UNESP]; Gameiro, M. O.; Padovani, Carlos Roberto [UNESP] (Springer, 2005)
The aim of this study was to evaluate the effect of intravaginal electrical stimulation (IES) on pelvic floor muscle (PFM) strength in patients with mixed urinary incontinence (MUI). Between January 2001 and February 2002, 40 MUI women (mean age: 48 years) were studied. Urge incontinence was the predominant symptom; 92.5% also presented mild stress urinary incontinence (SUI). Selection criteria were clinical history and urodynamics. Pre-treatment urodynamic study showed no statistical differences between the groups. Ten percent of the women in each group had involuntary detrusor contractions. Patients were randomly distributed, in a double-blind study, into two groups. Group G 1 (n=20), effective IES, and group G2 (n=20), sham IES, with follow-up at 1 month. The following parameters were studied: (1) clinical questionnaire, (2) examiner's evaluation of perineal muscle strength, (3) objective evaluation of perineal muscle by perineometry, (4) vaginal weight test, and (5) urodynamic study. The IES protocol consisted of three 20-min sessions per week over a 7-week period using a Dualpex Uro 996 at 4 Hz. There was no statistically significant difference in the demographic data of both groups. The number of micturitions per 24 h after treatment was reduced significantly in both groups. Urge incontinence, present in all patients before treatment, was reduced to 15% in G1 and 31.5% in G2 post-treatment. The subjective evaluation of PFM strength demonstrated a significant improvement in G1. Objective evaluation of PFM force by perineometer showed a significant improvement in maximum peak contraction post-treatment in both groups. In the vaginal weight test, there was a significant increase in average number of cone retentions post-treatment in both groups. With regard to satisfaction level, after treatment, 80% of the patients in G1 and 65% of the patients in G2 were satisfied. There was no statistically significant difference between the groups. There was a significant improvement in PFM strength from both effective and sham electrostimulation, questioning the effectiveness of electrostimulation as a monotherapy in treating MUI.
Keywords: controlled study; electrical stimulation; mixed urinary incontinence; treatment